Peran Berbagai Sumber N Terhadap Pertumbuhan dan Produksi Tiga Varietas Kedelai (Glycine Max (L.) Merril) di Lahan Kering - Adjie Putra Susetyo; Yaya Hasanah; Ferry Ezra Sitepu (Universitas Sumatera Utara, 2019)
Soybeans are a long-cultivated food commodity in Indonesia, which is currently not only positioned as a raw material for the food industry, but also a raw material for non-food industries. This study aims to determine the role of various sources of N on the growth and production of three varieties of soybean in dry land. This research was conducted at community land of Tanjung Anom Village Pancur Batu Subdistrict, Sumatera Utara which is at + 25 meters above sea level, on August to November 2016 using a Factorial Randomized Block Design with 2 factors. The first factor is the source of N consisted without nitrogen, N – Inorganic source (Urea), N – Biological source (Illetrisoy), and N – Organic Source (Biochar rice straw. The second factor is varieties with 3 types of varieties Cikurai, Grobogan, and Dering – 1. The observed variables were plant height, shoot dry weight, number of filed pods, seed dry weight per plant, , seed dry weight per plot and weight of 100 seeds. The result showed that varieties had significant effect on plant height at 2, 3, 5, and 6 week after plant (WAP), weight of 100 seeds and seed weight per plot and N source had significant effect on dry weight of canopy and number of pods. The interaction of varieties and N sources has no significant effect on all observed variables. Keywords: dry land, soybean, source N, varieties